Analysis of implementation of the KSK MBKM Program in Universitas 17 Agustus 1945 Surabaya - Pristiana, Ulfi; Nugroho, Mulyanto; Romadhan, Mohammad Insan; Haque, Sayidah Aulia’ul; Nafi, Maula; Sitohang, Arga Christian (Technium Social Sciences Journal, 2022)
In 2021, Universitas 17 Agustus 1945 Surabaya received KsK MBKM funding assistance for 6 study programs. This research was conducted to determine the impact of the implementation of the MBKM KsK program in the Untag Surabaya environment. The activities carried out were data collection by filling out questionnaires and conducting Focus Group Discussions (FGD) with MBKM implementing stakeholders at the University, namely the Head of Study Programs, Lecturers, Students, Education Staff, and Partners for the implementation of MBKM implementation. From the results of the questionnaire and FGD, in general the implementation of the KsK MBKM in each study program provides benefits for the Head of Study Programs and Lecturers because they support the preparation and review of the curriculum in accordance with the MBKM program. The study program also collaborates with partners to develop a scheme for off-campus activities. Education staff also supports MBKM activities, starting from the preparation of curriculum documents to preparing for the implementation of MBKM activities. Students are certainly very enthusiastic about participating in this MBKM activity, especially internship activities. What needs to be given more attention is the lack of insight from students, several lecturers, staff, and partners regarding the policies and SOP for MBKM activities made by both the University and Study Programs, so that in the future it is necessary to carry out a lot of socialization and education, as well as directly involve the students stakeholders to make MBKM activities at Untag Surabaya better.